An effect of single high dose of vitamin D3 on the risk of nosocomial infections, hospitalization time and mortality in hospitalized elderly population. A preliminary report - Leszczyńska, Dorota; Tuszyńska, Agata; Zgliczyńska, Magdalena; Zgliczyński, Wojciech; Misiorowski, Waldemar (Wiedza Medyczna, 2020)
Introduction: Observational studies indicate a significant impact of serum 25(OH)D concentration on incidence of hospital-acquired infections. However, we did not find any interventional study assessing the effect of vitamin D3 administration at the admission on the course of further hospitalization in internal medicine departments. Objective of the paper: Investigation of the impact of one-time high-dose vitamin D3 administration in elderly patients on the day of urgent admission to the hospital, on hospital-acquired infections. Materials and methods: A randomized, two-arms, open pilot study in 97 adults aged 60-100. A study group was given a single dose of 60,000 IU vitamin D3 and a control group was not subject to any intervention. Serum 25(OH)D and calcium were measured at the baseline and after 7 days. Results: 77.32% of studied patients were vitamin deficient, and among those, in 28.87% severe vitamin D deficiency was found. After single administration of 60,000 IU of vitamin D3, only 4 patients achieved recommended serum 25(OH)D concentration. The highest increase in serum 25(OH)D was observed in patients with severe deficiency. Numbers of observed nosocomial infections such as flu, hospital-acquired pneumonia or Klebsiella pneumoniae MBL+ infection did not differ significantly between study and control group, however there was a trend close to significance for lower incidence of Clostridium difficile infection in the vitamin D3 group. Conclusions: Preliminary results of the presented research indicate possible protective effect of single high dose of vitamin D3 against Clostridium difficile infection during hospitalization. Further research on larger group of patients, using higher dose of vitamin D3 is necessary.